Globalisering och internationalisering inom vetenskapen (Sociologisk Forskning, 1999)
Globalization or internationalization in the sciences.The main question in this study is whether we can find empirical evidence of globalization in science or not. Usually the increasing number of co-authorships in the sciences is seen as an indicator of increasing research collaboration, which in turn is seen as part of the globalization-trend. Here, this chain is questioned and the relation and the difference between globalization and internationalization in science is investigated and discussed. A number of studies have shown how the amount of research collaboration is increasing but it is not clear that this is actually leading to globalization in science rather than internationalization. Through a number of empirical results the structure of international research collaboration is described. It is concluded that there may very well be an ongoing globalization-trend but this is hardly evident in empirical studies of research collaboration. What can be seen though is a strengthened internationalization-trend. Globalization seems to be a phenomenon that ought to be used more carefully and studied through both bibliometric and other methods.